Metformin improves lipid metabolism disorders through reducing the expression of microsomal triglyceride transfer protein in OLETF rats. (December 2016) - Wang, Nianhong; Zhang, Junqing; Wu, Yiming; Liu, Jia; Liu, Lin; Guo, Xiaohui
Highlights: Type 2 diabetes mellitus are associated with lipid metabolism disorders which the pathogenic mechanism is not clear. In this study, increased expression of microsomal triglyceride transfer protein (MTP) was found in the liver of Otsuka Long Evans Tokushima Fatty (OLETF) rats. It suggested that MTP might be associated with the lipid metabolism disorder in OLETF rats. Metformin, as the first-line medication for the treatment of type 2 diabetes, could improve lipid metabolism through reducing the expression of MTP. Abstract: Objective: This study aimed to investigate the role of MTP on lipid metabolism disorders in insulin-resistant rats and the potential mechanism through which metformin can improve lipid metabolism disorders. Methods: 30 OLETF rats served as research subjects and 18 LETO rats of the same strain served as the control group (LETO group). After the first oral glucose tolerance test (at 8-week-old), 6 rats were randomly killed from each group. The remaining 24 OLETF rats were randomly divided into untreated group (OLETF group) and treated group (OLETF/M group, cured with metformin). By the end of the 10th and 20th week of treatment, MTP in the liver was measured for all rats in the study. Results: All OLETF rats exhibited diabetic phenotypes at 18-week-old, with their triglyceride level higher than in LETO rats at the same age. In OLETF rats, MTP level in the liver was higher than in LETO rats at 18-week-old, and the difference was significant at 28-week-old [(13.79 ± 1.47) vs. (8.20 ± 1.14), p < 0.05]. Treatment with metformin for 20 weeks decreased triglyceride [(1.06 ± 0.23) vs. (2.20 ± 0.62) mmol/L, p < 0.05] and total cholesterol [(1.90 ± 0.19) vs. (2.36 ± 0.14) mmol/L, p < 0.05] in OLETF rats. Metformin also decreased MTP level in the liver [(7.65 ± 1.31) vs. (13.79 ± 1.47), p < 0.01]. Conclusions: MTP may be associated with the lipid metabolism disorder in OLETF rats and metformin could improve lipid metabolism through reducing the expression of MTP.